Mild cognitive impairment and quality of life in the oldest old: a closer look - Hussenoeder FS; Conrad I; Roehr S; Fuchs A; Pentzek M; Bickel H; Moesch E; Weyerer S; Werle J; Wiese B; Mamone S; Brettschneider C; et al. (Springer Nature Switzerland AG, 2020)
Purpose Mild cognitive impairment (MCI) is a widespread phenomenon, especially affecting older individuals. We will analyze in how far MCI affects different facets of quality of life (QOL). Methods We used a sample of 903 participants (110 with MCI) from the fifth follow-up of the German Study on Ageing, Cognition, and Dementia in Primary Care Patients (AgeCoDe), a prospective longitudinal study, to analyze the effects of MCI on different facets of the WHOQOL-OLD. We controlled for age, gender, marital status, education, living situation, daily living skills, and the ability to walk, see, and hear. Results Univariate analyses showed that individuals with MCI exhibited lower QOL with regard to the facets autonomy; past, present, and future activities; social participation; and intimacy, but less fears related to death and dying. No significant difference was shown with regard to the facet sensory abilities. In multivariate analyses controlling for age, gender, marital status, education, living situation, daily living skills, and the ability to walk, see and hear, MCI-status was significantly associated with QOL in the facet autonomy. Conclusion Effects of MCI go beyond cognition and significantly impact the lives of those affected. Further research and practice will benefit from utilizing specific facets of QOL rather than a total score.
Keywords: MCI; Older people; Quality of life; WHOQOL-OLD; Activities of Daily Living; Aged; Aged, 80 and over; Aging; Cognition; Cognitive Dysfunction; Dementia; Female; Humans; Longitudinal Studies; Male; Primary Health Care; Prospective Studies; Quality of Life